(untitled) (The International Journal of Educational Sciences and Arts, 2026)
This article examines the procedure of destroying political prison records carried out by the apartheid government and its executive and security agencies during the period of political transition preceding the formal shift to a democratic system in South Africa. The analysis explores the impact of the absence of administrative documentation on the writing of the history of political prisons and traces the relationship between record destruction, individual testimony, and the disappearance of the official register within historical narrative. It relies on an analytical reading of Chapter Eight of the Truth and Reconciliation Commission Report, alongside testimonies of former political prisoners and selected studies on archives, in order to trace the transformation of the tools used to write the history of political prisons following the disappearance of the administrative record. The article demonstrates that the destruction of records altered the conditions under which the history of political prisons is written by disrupting the possibility of tracing decisions and procedures within the administrative apparatus organized and implemented by the prison administration of the apartheid state and its security agencies. This absence compelled historians to rely extensively on individual testimony in reconstructing the prison experience. While such testimony preserved crucial details of daily life inside prisons, it remained limited in its ability to reveal the administrative structures that governed detention and regulated its procedures. The resulting absence of records redirected historical writing toward the description of lived experience and constrained the analysis of the relationship between prisons, state ministries, and their written procedures and defined responsibilities. The article concludes that the disappearance of documentation resulted from administrative decisions taken during the transitional period and had a direct impact on the writing of the history of political prisons. This absence exposes the limits of institutional analysis and transfers a substantial documentary burden to individual testimony. It thus confronts the historian with a precise methodological task that requires reading testimony in light of what is missing from the administrative organization and incorporating the absence of records as a condition shaping historical analysis.